Population - Nardo, Don, 1947- (San Diego, CA : Lucent Books, 1991)
Considers the global consequences of continued population growth and the various options for dealing with its impact on the environment and natural resources.
Includes bibliographical references (p. 90-92) and index.
Keywords: Population -- Juvenile literature; Population policy -- Juvenile literature; Population